2022
DOI: 10.1021/acssuschemeng.1c07179
|View full text |Cite
|
Sign up to set email alerts
|

Electron Irradiation Induces the Conversion from 2H-WSe2 to 1T-WSe2 and Promotes the Performance of Electrocatalytic Hydrogen Evolution

Abstract: Hydrogen (H2) is an environment-friendly clean energy. In recent years, novel hydrogen evolution electrocatalysts have attracted extensive attention in the scientific community. In this work, the conversion of 2H phase tungsten selenide (2H-WSe2) into 1T phase tungsten selenide (1T-WSe2) was induced by 1 MeV electron irradiation to improve its electrocatalytic performance. When the irradiation fluence is 5 × 1014 e/cm2, the minimum initial overpotential of WSe2 is 101 mV lower than the initial overpotential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…They are semiconductors in the stable 2H phase and their band structures change from an indirect bandgap for bulk materials or multilayer nanosheets to a direct bandgap for monolayer nanosheets, whereas the metastable 1T phase demonstrates metallic electronic properties. The tunable band structures based on different numbers of layers and phases result in tunable electronic and optical properties such that TMDCs are broadly applied in semiconductor devices, [ 2–4 ] catalysts, [ 5–8 ] batteries, [ 9–12 ] solar cells, [ 13–15 ] etc.…”
Section: Introductionmentioning
confidence: 99%
“…They are semiconductors in the stable 2H phase and their band structures change from an indirect bandgap for bulk materials or multilayer nanosheets to a direct bandgap for monolayer nanosheets, whereas the metastable 1T phase demonstrates metallic electronic properties. The tunable band structures based on different numbers of layers and phases result in tunable electronic and optical properties such that TMDCs are broadly applied in semiconductor devices, [ 2–4 ] catalysts, [ 5–8 ] batteries, [ 9–12 ] solar cells, [ 13–15 ] etc.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that the defects in MoS 2 are mainly S vacancies. Under ion irradiation, MoS 2 generates S vacancies more readily than Mo vacancies, consistent with the literature. ,, Electron paramagnetic resonance (EPR) was also performed on as-prepared MoS 2 and F – -2 × 10 13 . As shown in Figure S8, the characteristic peak of the Mo–S dangling bonds can be clearly detected at ∼3339 G, and the g -factor of this resonance is estimated to be 2.003.…”
Section: Resultsmentioning
confidence: 99%
“…With an increase in fluence, the concentration of F doping and S vacancies also proportionally increase, leading to optimal HER performance of MoS 2 when the fluence is 2 × 10 13 ions/cm 2 . However, with a further increase in fluence to 5 × 10 13 ions/cm 2 , the HER performance of MoS 2 is suppressed, which is attributed to excessive exposure to irradiation, which severely damages the MoS 2 lattice structure, leading to the generation of a large number of disordered regions and subgrain boundaries . On the one hand, previous studies have reported that MoS 2 NSs with lower crystallinity exhibit more grain boundaries, and S vacancies located in or close to grain boundaries are not very active, leading to worse catalytic performance .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, T’-phase TMDs with metallic characteristics have considerably high catalytic activity resulting from their high electron conductivity and abundant active sites both at the surface areas and edges [ 46 , 47 , 48 , 49 ]. Thus, phase transition engineering has become an effective pathway to improve catalytic performance [ 27 , 28 , 29 , 50 ]. Theoretical analysis results have displayed that the T’-TMDs are a potential candidate catalyst material for HER, especially for T’-MoSe 2 and T’-WS 2 with a hydrogen adsorption free energy (Δ G H* ) of −0.04 eV and 0.03 eV, respectively [ 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%